Mitochondrial DNA sequence variations in populations of Sardinapilchardus(Walbaum 1792) along the Tunisian coasts - FADHLAOUI-ZID, ΚARIMA (Mediterranean Marine Science, 2019)
Sardine is a fish species of great economic importance to Tunisia. Knowledge of genetic diversity and population distribution is essential for an efficient management and sustainability of any regional fishery. This study aimed to assessing the genetic structure and to specify the stocks of the European sardine (Sardina pilchardus). To this end, 83 specimens were collected from three localities along the Tunisian coast and analysed using mitochondrial DNA sequences. The results of sequence analysis determined the existence of variations in 40 single nucleotide sites within the 307 bp fragment of the cytb gene examined and defined twenty different haplotypes. Genetic diversity, estimated by haplotypic diversity, was high in all samples. Tunisian S.pilchardus samples show some level of genetic structuring. First, genetic differentiation between localities (ΦST estimates) was significant for all comparison. Second, the analysis of molecular variance AMOVA indicates a high level of genetic variation (ΦST = 0.093; P<0.001). The structural patterns identified can be explained largely in relation to the regional oceanographic features. In conclusion, this study provided initial genetic data in making inference of the genetic structure of S. pilchardus along the Tunisian coasts.